Dramaturgia Nikołaja Kolady i jekaterynburgska bohema na łamach czasopisma Didaskalia w latach 2000-2003 - Strycharski, Jarosław (Acta Polono-Ruthenica, 2007)
In the article the author examines sparse mentions of the modern Russian drama which development has progressed much in Yekatirenburg. An analysis of the articles mentioning the modern drama proves the author’s statement about N. Kolada, having educated a group of talented playwrights and being the most popular modern dramatist in Russia as well as abroad in spite of his peculiar aesthetic and poetic outlook.